Strukturwandel im Bankenwesen und regionalwirtschaftliche Implikationen: Konzeptionelle Ansätze und empirische Befunde - Klagge, Britta (ERDKUNDE, 1995)
The influence of the banking system is often neglected when dealing with regional structures and disparities. The banking system, however, does play an important role for regional development. By looking at the functional, organizational and spatial aspects of the ongoing structural changes in the banking sector, the consequences for retail and corporate commercial banking are examined. Special emphasis is put on the interrelationship between locational structures, integration with other subjects and regional processes. Three approaches are applied: organizational-structural, input-orientated and output-orientated. Changes in the banking sector take place both in the structure of the sector as a whole and with regard to the organization and functionality within banks. From a geographical point of view the concentration processes and the restructuring of the sales organization are most relevant. The latter includes the downsizing and reorganization of the branch network and the rapid development of alternative, mostly telecommunicative modes of distribution. Restructuring results in an increasing spatial differentiation, which is based on the profitability of regions and client groups. These and other changes within the banks affect the structure and spatial pattern of employment and demand for goods and services. These development are advantageous mainly to national financial centers as opposed to regional financial centers and peripheral areas. Only peripheral regions that are able to attract back-office functions may profit. While the regional effects on the input side of banks are relatively easy to understand this is not the case for the regional effects exercised through the sales of banking services. This is due to the unwillingness of banks to publish sales data differentiated by regions. Nevertheless the distribution of credit as one main outcome of banking activities is especially important for regional development because of its stimulating effect on regional investment and growth rates. The lack of relevant data gives theoretical considerations a greater weight. However, it is possible to isolate several factors that influence the regional pattern of credit distribution. These factors include the size structure of the banking sector and its spatial distribution. With respect to these two factors, empirical findings indicate that from a regional policy point of view, decentralized but integrated banking systems offer the greatest advantage.